MA11 Dose Effects on Liquid Organic Fertilizer from Cattle and Goat Urine - Pramana, Andrey Febri; Yakin, Engkus Ainul (Jurnal Biologi Tropis, 2026)
This study investigated the effect of different doses of MA11 microorganisms on the quality of liquid organic fertilizer (LOF) produced from a mixture of cow and goat urine based on nitrogen (N), phosphorus (P), potassium (K), and pH. A Completely Randomized Design (CRD) was employed with three treatments: P0 (100 mL MA11), P1 (200 mL MA11), and P2 (300 mL MA11), each with four replications. Data were analyzed using one-way analysis of variance (ANOVA), followed by Duncan’s multiple range test at the 5% significance level. The results showed that MA11 dosage significantly affected (P < 0.05) the N, P, K, and pH of the LOF. Increasing the MA11 dose increased nutrient concentrations, with nitrogen rising from 0.033% to 0.063%, phosphorus from 0.055% to 0.107%, and potassium from 0.032% to 0.077%, while pH decreased from 4.32 to 4.03. Treatment P2 (300 mL MA11) produced the highest N, P, and K contents and the lowest pH. The pH value met the Indonesian quality standard for liquid organic fertilizer (4–9). These findings indicate that the application of 300 mL MA11 improved the nutrient characteristics of liquid organic fertilizer derived from cow and goat urine under the conditions of this study.